2021
DOI: 10.1016/j.compbiomed.2021.104669
|View full text |Cite
|
Sign up to set email alerts
|

Decrypting the role of predicted SARS-CoV-2 miRNAs in COVID-19 pathogenesis: A bioinformatics approach

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), is a highly transmissible virus causing the ongoing global pandemic, COVID-19. Evidence suggests that viral and host microRNAs play pivotal roles in progression of such infections. The decisive impact of viral miRNAs and their putative targets in modulating the transcriptomic profile of its host, however remains unexplored. We hypothesized that the SARS-CoV-2 derived miRNAs can potentially play a contributory role in its pathogenicity and aid in its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…The key miRNAs identified (miR-4433b-5p, miR-6780b-3p, miR-6883-3p, miR-320b, miR-7111-3p, miR-4755-3p, miR-320c, and miR-6511a-3p) in this study were found to be involved in PI3K/AKT, Wnt/β-catenin, and STAT3 signaling pathways. Interestingly, similar pathways have been reported to be significantly associated signaling pathways in SARS-CoV2 infection in a bioinformatics analysis conducted by our lab on publicly available datasets [ 15 ]. The findings of this new study urge the need for further study on a larger number of participants.…”
Section: Non-coding Rnas In Covid-19supporting
confidence: 58%
“…The key miRNAs identified (miR-4433b-5p, miR-6780b-3p, miR-6883-3p, miR-320b, miR-7111-3p, miR-4755-3p, miR-320c, and miR-6511a-3p) in this study were found to be involved in PI3K/AKT, Wnt/β-catenin, and STAT3 signaling pathways. Interestingly, similar pathways have been reported to be significantly associated signaling pathways in SARS-CoV2 infection in a bioinformatics analysis conducted by our lab on publicly available datasets [ 15 ]. The findings of this new study urge the need for further study on a larger number of participants.…”
Section: Non-coding Rnas In Covid-19supporting
confidence: 58%
“…In this scenario, the efforts in optimizing vaccination strategies need to be associated with efforts in establishing “ready-to-use” therapeutic strategies for symptomatic patients for which a definite cure is still missing. In this regard, much effort has been recently made to elucidate the molecular mechanisms and intracellular pathways mostly involved in both SARS-CoV-2 infection and COVID-19 pathophysiological processes; also by using bioinformatics approaches ( Alnajeebi et al, 2022 ; Hasankhani et al, 2021 ; Kwan et al, 2021 ; Rahaman et al, 2021 ). These studies have shown that genes related to immune and apoptosis-related functions were deregulated, and further analysis revealed that p53 signaling was one of the most enriched pathway upon SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Rahaman et al [64] applied a series of computational tools to predict 34 SARS-CoV-2encoded miRNAs and their presumptive targets in human host; the immune and apoptotic pathways were selected as the most represented pathways (p53 signaling, cytokine receptor interaction, toll-like receptor (TLR) signaling, NOD-like receptor signaling and Jak-STAT signaling). A further investigation employing a dataset of SARS-CoV-2-infected cells revealed that 46 genes related to immune and apoptosis functions were deregulated during viral infection.…”
Section: Viral Mirnas-human Host Interactionmentioning
confidence: 99%